Respiration Monitoring Using Humidity Sensor Based on Hydrothermally Synthesized Two-Dimensional MoS2 - Gwangsik Hong; Mi Eun Kim; Jun Sik Lee; Ja-Yeon Kim; Min-Ki Kwon (Nanomaterials)
Breathing is the process of exchanging gases between the human body and the surrounding environment. It plays a vital role in maintaining human health, sustaining life, and supporting various bodily functions. Unfortunately, current methods for monitoring respiration are impractical for medical applications because of their high costs and need for bulky equipment. When measuring changes in moisture during respiration, we observed a slow response time for 2D nanomaterial-based resistance measurement methods used in respiration sensors. Through thermal annealing, the crystal structure of MoS2 is transformed from 1T@2H to 2H, allowing the measurement of respiration at more than 30 cycles per minute and enabling analysis of the response. This study highlights the potential of two-dimensional nanomaterials for the development of low-cost and highly sensitive humidity and respiration sensors for various applications.